The Effect of Head Position on Buccal Cortical Bone Thickness Measurements in CBCT Scans: A Human Dry Mandible Study - Çelik, Berrin; Üçok, Cemile Özlem (European Journal of Therapeutics, 2024)
Objective: The aim of this study was to compare buccal cortical bone thickness measurements on cone beam computed tomography (CBCT) scans of human dry mandibles with direct measurements and to evaluate the effect of different head positioning on measurements. Methods: In total, direct linear measurements were made at reference points on the buccal bone surfaces in toothless sockets in 26 human dry mandibles. CBCT scans were performed in the central position and with four different types of head position (to the right-left, to the anterior-posterior). Thickness measurements were performed on cross-sectional sections from relevant areas where heated gutta-percha was placed. Measurements were summarized as mean±standard deviation. Differences between measurements were analyzed by ANOVA and Friedmann test. Results: Compared to direct measurements, buccal cortical bone thickness in CBCT scans was higher in the incisor and premolar regions, while lower values were obtained in the molar region. These differences were statistically significant but less than 0.2 mm (p<0.005). Different head positions had no effect on measurements on CBCT images (p>0.005). Intraobserver agreement for buccal bone thickness was found to be high (ICC=0.902-0.976). Conclusion: It demonstrated a clinically acceptable difference between direct measurements and CBCT measurements of mandibular buccal cortical bone thickness. Additionally, no differences in measurements were observed between different types of head positions.